Educational Value and Teaching Strategies of Traditional Chinese Revolutionary Works: Taking High School Chinese Teaching as an Example - WANG Zhen; MA Shaoxi (Jiaoshi jiaoyu xuebao)
Traditional Chinese revolutionary works contain unique educational value, but they have not received the attention they deserve in teaching practice. To deeply explore and fully exert the educational potential of Chinese revolutionary works, Chinese teachers should take the guidance of Xi Jinping's Thought of Socialism with Chinese Characteristics for a New Era, follow national policies such as the "Guidelines for Introducing Revolutionary Traditions into Curriculum Materials for Primary and Secondary Schools, " adhere to the "Ordinary High School Chinese Curriculum Standards (2017 Edition, Revised in 2020), " rely on the unified high school Chinese textbooks, be oriented by the current situation of high school Chinese teaching, and fully tap into the potential of Chinese revolutionary words form four dimensions: moral education value, aesthetic education value, historical value, and cultural value. The four dimensions hold structural characteristics of integrity, hierarchy, interactivity, and generativity. They are interrelated, interdependent, and mutually generated, jointly stimulating the educational potential of traditional Chinese revolutionary works. Teachers should integrate text resources, create teaching scenarios, and orderly organize practical activities, in order to effectively realize the educational value of traditional Chinese revolutionary works, enhance students' recognition of the value of these works, and enable them to continue the red bloodline, practice the revolutionary spirit, and ultimately grow into socialist builders and successors with comprehensive development of morality, intelligence, physical fitness, aesthetics, and labor.